2018
DOI: 10.1002/ctpp.201800113
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional magnetosonic shock wave propagation in dense electron–positron–ion plasmas

Abstract: Two-dimensional (2D) magnetosonic wave propagation in magnetized quantum dissipative plasmas is studied. The plasma system is comprised of inertial ions, inertia-less electrons, and positrons. The multi-fluid quantum hydrodynamic model is used, in which quantum statistical and quantum tunnelling effects of electrons and positrons are included. Reductive perturbation analysis is performed to derive the Zabolotskaya-Khokhlov equation for the 2D propagation of a magnetosonic shock wave in a magnetized qauntum pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…It was discovered that the shock wave shapes are considerably altered by the presence of positrons in plasma. Various models are used to explore the motion of electrostatic solitary waves in e-p-i plasma in multiple studies [8][9][10][11][12][13]. Many studies of ion acoustic solitons (IASs) in electron-positron-ion (e-p-i) plasmas have been described in recent years [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered that the shock wave shapes are considerably altered by the presence of positrons in plasma. Various models are used to explore the motion of electrostatic solitary waves in e-p-i plasma in multiple studies [8][9][10][11][12][13]. Many studies of ion acoustic solitons (IASs) in electron-positron-ion (e-p-i) plasmas have been described in recent years [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[46,47] KP equation is such an integrable equation and hence Ma et al [48] has obtained a class of lump solutions to the (2 + 1)-dimensional Kadomtsev-Petviashvili (KP) equation by using Hirota bilinear form. The wide prevalence of lump soliton solutions to nonlinear evolution equations, specifically to KP equation, attracts many researchers [49][50][51][52] to reveal its impressive nonlinear significance.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the positron existence in plasma significantly modifies the shock wave profiles. Numerous investigations are carried out to study the propagation of electrostatic solitary waves in e‐p‐i plasma using different models . Khan et al theoretically investigated the analytical and numerical perspectives of ion acoustic solitary in electron‐positron‐ion quantum plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations are carried out to study the propagation of electrostatic solitary waves in e-p-i plasma using different models. [10][11][12][13][14][15] Khan et al [16] theoretically investigated the analytical and numerical perspectives of ion acoustic solitary in electron-positron-ion quantum plasma. They studied the impact of the positron concentration and geometry factor on ion acoustic shock waves.…”
Section: Introductionmentioning
confidence: 99%